(untitled) (Sociologisk Forskning, 1993)
A picture of the deteriorating situation for women in Iran After the Islamic Revolution in Iran 1978-79, the situation has become much worse for women, in terms of rights and resources. The aim of this article is to describe this change with the help of demographic data and to argue that it is the result of the repressive policy of the Islamic regime and, ultimately, of islamic ideology. In particular, Iranian women suffer from the return to more traditional laws of marriage and from reduced opportunities to get an education, or a job.